Comparison of Clinical Outcomes in Patients with Active Cancer Receiving Rivaroxaban or Low-Molecular-Weight Heparin: The OSCAR-UK Study - Cohen, Alexander T.; Wallenhorst, Christopher; Rivera, Marcella; Ay, Cihan; Schaefer, Bernhard; Abdelgawwad, Khaled; Psaroudakis, George; Brobert, Gunnar; Ekbom, Anders; Lee, Agnes Y. Y.; Khorana, Alok A.; Becattini, Cecilia; Carrier, Marc; Coleman, Craig I.; Martinez, Carlos (Thrombosis and Haemostasis, 2024)
Background In most patients with cancer-associated venous thromboembolism (CT), essentially those not at high risk of bleeding, guidelines recommend treatment with direct oral anticoagulants as an alternative to low-molecular-weight heparins (LMWHs). Population-based studies comparing these therapies are scarce.Objectives To compare the risk of venous thromboembolism (VTE) recurrences, significant bleeding, and all-cause mortality in patients with CT receiving rivaroxaban or LMWHs.Patients/Methods Using UK Clinical Practice Research Datalink data from 2013 to 2020, we generated a cohort of patients with first CT treated initially with either rivaroxaban or LMWH. Patients were observed 12 months for VTE recurrences, significant bleeds (major bleeds or clinically relevant nonmajor bleeding requiring hospitalization), and all-cause mortality. Overlap weighted sub-distribution hazard ratios (SHRs) compared rivaroxaban with LMWH in an intention-to-treat analysis.Results The cohort consisted of 2,259 patients with first CT, 314 receiving rivaroxaban, and 1,945 LMWH, mean age 72.4 and 66.9 years, respectively. In the 12-month observational period, 184 person-years following rivaroxaban and 1,057 following LMWH, 10 and 66 incident recurrent VTE events, 20 and 102 significant bleeds, and 10 and 133 deaths were observed in rivaroxaban and LMWH users, respectively. The weighted SHR at 12 months for VTE recurrences in rivaroxaban compared with LMWH were 0.80 (0.37–1.73); for significant bleeds 1.01 (0.57–1.81); and for all-cause mortality 0.49 (0.23–1.06).Conclusion Patients with CT, not at high risk of bleeding, treated with either rivaroxaban or LMWH have comparable effectiveness and safety outcomes. This supports the recommendation that rivaroxaban is a reasonable alternative to LMWH for the treatment of CT.
Keywords: venous thromboembolism; anticoagulants; cancer